Democracy's "Lawless music": the Whitmanian moment in the U.S. construction of representative literariness - Leypoldt, Günter (New literary history, 2007)
This essay explores the connection between Walt Whitman and the rhetorical uses of “representative literariness,” as part of a “post-Kantian” symbolic repertoire of intellectual self-legitimation. My focus lies on American literary studies, where representative literariness emerges as an important critical concept during the construction of an iconic Walt Whitman, beginning in the 1870s, and culminating in the 1940s, when both Whitman and his “age” were refigured in terms of aesthetic modernism and became central to the idea of an American Renaissance. While the American-Renaissance concept lost its critical appeal during the 1970s, its underlying notion of representative literariness has retained some of its cultural centrality.
Gesehen am 07.10.2019